Harmoni dalam budaya Jawa - Roqib, Muhammad (Pustaka pelajar, 2007)
On harmonious life from Javanese culture perspective
Includes bibliographical references (S. 245-254)
Keywords: œaJavanese (Indonesian people)œxSocial life and customs; œaEthics; Javanese; Kultur; Harmonie